2008
DOI: 10.1038/eye.2008.211
|View full text |Cite
|
Sign up to set email alerts
|

Successful surgical treatment of optic disc pit maculopathy

Abstract: patients with scleritis develop bilateral disease, 50% of whom have delayed onset in the fellow eye, mostly of the same type of scleritis. 8 A high index of suspicion may uncover this sight-threatening but treatable condition. Occasionally a patient with medical training will experience the symptoms of a disorder that may provide a unique opportunity to determine the exact nature of the symptom. This has occurred in the past with lightning flashes from posterior vitreous detachment (PVD) because Moore publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…Differences in techniques result from the selection of adjuvant procedures such as short or long-acting gas tamponade, ILM peeling, endolaser photocoagulation in the peripapillary area and drainage of subretinal fluid. [27][28][29][30]33,[35][36][37][40][41][42][43][44][45][46][47] Hirakata et al 22 reported favourable results in 10 out of 11 patients treated with vitrectomy and gas exchange without endolaser photocoagulation. Hirakata et al 36 have also recently reported good surgical outcomes with vitrectomy but without laser treatment or gas tamponade for macular detachment with an optic disc pit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Differences in techniques result from the selection of adjuvant procedures such as short or long-acting gas tamponade, ILM peeling, endolaser photocoagulation in the peripapillary area and drainage of subretinal fluid. [27][28][29][30]33,[35][36][37][40][41][42][43][44][45][46][47] Hirakata et al 22 reported favourable results in 10 out of 11 patients treated with vitrectomy and gas exchange without endolaser photocoagulation. Hirakata et al 36 have also recently reported good surgical outcomes with vitrectomy but without laser treatment or gas tamponade for macular detachment with an optic disc pit.…”
Section: Discussionmentioning
confidence: 99%
“…Although various surgical techniques with different success rates have been reported in literature, [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] PPV with gas endotamponade seems to be the preferred procedure when surgery is selected. Differences in techniques result from the selection of adjuvant procedures such as short or long-acting gas tamponade, ILM peeling, endolaser photocoagulation in the peripapillary area and drainage of subretinal fluid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We reported a successful anatomical outcome with improvement of visual acuity from counting fingers to 6/18 [6].…”
Section: Discussionmentioning
confidence: 80%
“…Treatment modalities reported for ODP maculopathy include various combinations of PPV, gas tamponade, laser photocoagulation to the temporal juxtapapillary area, internal limiting membrane (ILM) peeling, internal drainage of submacular fluid or macular scleral buckling procedure [4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%